Half-plane contact problems in partial slip with varying normal and tangential loads - Truelove, J; Blades, L; Hills, D (Elsevier, 2022)
Simple methods of finding the transient and steady state stick zones for frictional contacts subject to varying normal and shear forces are discussed. Particular emphasis is given to the Hertzian contact because the algebra is very simple for this geometry, but the methods and results may be carried over to any other contact geometry that can be solved within the framework of half plane theory, including the widely-occurring flat contact with radiused edges.